The role of S1P receptors and their interacting proteins in Krabbe Disease - O'Sullivan, Catherine (Trinity College (Dublin, Ireland). Department of Physiology, 2015)
Globoid cell leukodystrophy (Krabbe disease, KD) is a rare autosomal recessive neurodegenerative disorder that presents within the first six months of life and is usually fatal by the age of two years. KD is caused by a deficiency in the lysosomal enzyme galactocerebrosidase (GALC), which results in the accumulation of the toxic metabolite psychosine in the brain. Here we investigated the ability of psychosine to directly induce hallmarks of KD, in vitro, focusing on increased levels of glial cell death, mitochondrial dysfunction, pro-inflammatory cytokines and demyelination. Importantly we also demonstrate reversal of these effects by the sphingosine 1- phosphate receptor (SIPR) agonist pFTY720 (Fingolimod) (Results 1). We additionally investigated effects of an S1PR1/S1PR5 agonist called BAF312 on psychosine-induced toxicity in isolated astrocyte and microglia cultures as well as in slice culture models of demyelination.
Keywords: Molecular Neuropharmacology, Ph.D.; Ph.D. Trinity College Dublin.